Development of a Comic System for Human Digestive Education to Improve Critical Thinking Abilities - Pangesti, Yuli Dwi; Andriani, Aldina Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The use of technology-based learning media in stories and pictures has not been optimally used by teachers, which causes students' critical thinking skills to be low. This study aims to describe the development design and test the feasibility and effectiveness of Education Comic for the human digestive system to improve the critical thinking skills of SDN Patemon 02 Semarang grade V students. This type of research is research and development (R&D) with the ADDIE model. The stages of ADDIE are as follows: (1) Analyze, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data collection techniques used were Test (pretest and post-test) and Non-test (interview, observation, questionnaire, and document data). The research subjects were 20 students in SDN Patemon 02 Semarang class V. The data analysis technique uses normality, t-tests, and N-gain tests. The study results show that (1) The development design of the educational comic uses the Adobe Photoshop CS3 application and Clip Studio Paint with components consisting of a cover, character introduction, reading instructions, materials, and evaluation. (2) The feasibility results of education comics from material experts with 90% of the category are very feasible, media experts are 90% of the category very feasible with the results of the questionnaire responses of students and teachers of 98.56%, 90.55%, and 96.67% respectively with the category of very feasible. (3) the effectiveness of the Education comic is shown from the t-test results obtained a significance value of 0.00, which means <0.05, then the hypothesis is accepted. The improvement in critical thinking skills is shown from the results of the N-gain test of 77.64% with the high category. The conclusion of this study shows that the Human Digestive System Education Comic has been successfully developed, feasible, and effective in improving the critical thinking skills of grade V students of SDN Patemon 02 Semarang.